KONSEP KAJIAN FILSAFAT ILMU DAN ILMU FILSAFAT PERSPEKTIF PENDIDIKAN ISLAM - Yudistira Nugraha, Muhammad; Rahmania, Elvina; Yolanda; Ibrahim, Duski; Syarnubi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to find out how the concept of studying philosophy of science and philosophy of science from the perspective of Islamic education. The type of research used, namely library research, is a method of collecting data by seeking to understand and learn theories from various literature related to the research being studied, the source is in the form of books and websites referring to literature in line with the discussion of the research. The approach used is